Can blood amyloid levels be used as a biomarker for Alzheimer's disease?. Issue 1 (March 2021) - Yang, Yuan-Han; Situmeang, Rocksy FV; Ong, Paulus Anam
Alzheimer's disease (AD) increasingly affects society due to aging populations. Even at pre‐clinical stages, earlier and accurate diagnoses are essential for optimal AD management and improved clinical outcomes. Biomarkers such as beta‐amyloid (Aβ) or tau protein in cerebrospinal fluid (CSF) have been used as reliable markers to distinguish AD from non‐AD, and predicting clinical outcomes, to attain these goals. However, given CSF access methods' invasiveness, these biomarkers are not used extensively in clinical settings. Blood Aβ has been proposed as an alternative biomarker since it is less invasive than CSF; however, sampling heterogeneity has limited its clinical applicability. In this review, we investigated blood Aβ as a biomarker in AD and explored how Aβ can be facilitated as a viable biomarker for successful AD management.